Is jazz popular music? - Frith, Simon (Jazz Research Journal, 2007)
This paper addresses a paradox: as a matter of cultural and musical history jazz was clearly the most significant form of twentieth-century popular music and yet within the academy ‘popular music studies’ and ‘jazz studies’ are quite distinct scholarly associations and approaches. How can we account for this? Three lines of enquiry are followed: the history of popular music studies as a scholarly field; the current status of jazz in the marketplace; the attitude of jazz musicians and writers to ‘the popular’. It is concluded that if jazz scholars regard popular music studies as irrelevant to their concerns then for that very reason popular music scholars need to take account of jazz.